Optimal unemployment insurance requirements - Gustavo De Souza; André Victor Doherty Luduvice (Federal Reserve Bank of Chicago, 2022)
In the US, workers must satisfy two requirements to receive unemployment insurance (UI): a tenure requirement of a minimum work spell and a monetary requirement of a past minimum earnings. Using discontinuity of UI rules at state borders, we find that the monetary requirement decreases the number of employers and the share of part-time workers, while the tenure requirement has the opposite effect. In a quantitative model, the monetary requirement induce workers to search longer because low paying jobs are not covered by UI. Since it mitigates moral hazard, the optimal UI design has a high monetary requirement.
Keywords: E24; E61; J65; 330; Unemployment Insurance; UI Eligibility; Optimal UI